Aleksandr Nevskii - Eisenstein, Sergei (Soviet Union, 1938)
The 13th century. The warriors of the powerful Teutonic Order have occupied Pskov and are advancing towards the center of Russia. Prince Alexander Nevsky undertakes to lead the troops of Great Novgorod, defeating the Teutonic army on Lake Chudskoe.
Keywords: Fiction films